Ensemble Learning Algorithms based on Road Accident Data Prediction - Reddy Gondi Konda; Vullam Nagagopi Raju; Sekhar G. Soma; Sundaragiri Dheeraj; Shaik Subhani (ITM Web of Conferences)
Road accidents are common nowadays due to traffic, and road conditions. It affected life threats to propel lives. So to follow instructions of specific road conditions and safe driving. All this information about accidents, to learn lessons from these incidents and implement novel strategies to avoid accidents under any conditions. Environmental factors also play a key role in road accidents even if drivers are carefully driving vehicles. In our research paper, we construct an accident prediction model using ensemble machine learning techniques. Due to this classification system to implement of safety measures and accident prediction. Different types of elements like weather, road conditions, lighting, and vehicle conditions are used to predict road accidents. Our dataset’s attributes are accidents, vehicles, and casualties. Our statistical results generate Logistic Regression, which gives the highest accuracy rate among all machine learning algorithms.